Mesenchymal Stem Cells With Modification of Junctional Adhesion Molecule A Induce Hair Formation - Wu, Minjuan (AlphaMed Press, 2014)
The junctional adhesion molecule A (JAM-A) has been shown to serve a crucial role in the proliferation, differentiation, and tube-like formation of epithelial cells during angiogenesis. The role of JAM-A in hair follicle (HF) regeneration has not yet been reported. In this study, we used human JAM-A-modified human mesenchymal stem cells (MSCs) to repair HF abnormalities in BALB/c nu/nu mice. The JAM-A gene and JAM-A short hairpin RNA were transfected into cultured human MSCs to generate the JAM-A overexpression MSCs (JAM-A(ov) MSCs) and JAM-A knockdown MSCs (JAM-A(kd) MSCs), respectively. These cells were injected intradermally into the skin of nude mice during the first telogen phase of the HF that occurs 21 days postnatally. We found that JAM-A(ov) MSCs migrated into the HF sheath and remodeled HF structure effectively. The HF abnormalities such as HF curve and HF zigzag were remodeled, and hair formation was improved 7 days following injection in both the JAM-A(ov) MSC and MSC groups, compared with the JAM-A(kd) MSC group or negative control group. Furthermore, the JAM-A(ov) MSC group showed enhanced hair formation in contrast to the MSC group, and the number of curved and zigzagged HFs was reduced by 80% (p < .05). These results indicated that JAM-A(ov) MSCs improved hair formation in nude mice through HF structure remodeling.